2014
DOI: 10.5588/pha.14.0042
|View full text |Cite
|
Sign up to set email alerts
|

Poor treatment outcomes among multidrug-resistant tuberculosis patients in Gomel Region, Republic of Belarus

Abstract: Treatment outcomes among MDR-TB patients were poor, with high rates of death, failure and loss to follow-up (including pre-treatment loss to follow-up). Urgent measures to increase ART uptake among HIV-infected MDR-TB patients, improved access to second-line anti-tuberculosis drug susceptibility testing and comprehensive patient support measures are required to address this grim situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
1
13
1
1
Order By: Relevance
“…20,21 Such patients are very difficult to manage and are more at risk of adverse outcomes. The NTP needs to control the irrational use of SLDs and take firm steps to ban over-the-counter sales of both FLDs and SLDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Such patients are very difficult to manage and are more at risk of adverse outcomes. The NTP needs to control the irrational use of SLDs and take firm steps to ban over-the-counter sales of both FLDs and SLDs.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Age-specific treatment strategies are needed to improve outcomes in older age patients. We also observed that patients with a history of anti-tuberculosis treatment in the private sector were more likely to have unfavourable treatment outcomes than those treated in the public sector (OR 1.53, 95%CI 1.16-2.02).…”
Section: Discussionmentioning
confidence: 99%
“…However, a 2012 individual patient data meta-analysis found a higher proportion of 23% [26]. A rough literature review has revealed that the proportion of MDR TB patients who were LTFU ranges from 2.2 to 47% [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The figures vary vastly among different years, countries, and institutions, suggesting that the underlying factors responsible for these variations should be studied carefully.…”
Section: Proportion Of Ltfumentioning
confidence: 99%
“…XDR-TB can be primarily transmitted from person to person or secondary to the development through high bacillary load, inadequate treatment (poor compliance, iatrogenic, drug stock outs, programatic weakness), low body mass index, or previous failures [34][35][36][37][38]. Prevention of the development of drug-resistant TB is essential given the recent worldwide increase in incidence.…”
Section: Prevention Of Xdr-tb During Mdr-tb Treatmentmentioning
confidence: 99%